The effects of education on health and fertility in Ghana - Ahene-Codjoe, Ama Asantewah (2012)
Using the Ghana Living Standards Survey (GLSS) conducted in 1987/88 and 1998/99, this thesis examines two thematic areas of non-monetary returns to education in Ghana. One of the primary aims is to find the differences in the effects of education over the decade (1987/88–1998/99), using standard and non-standard econometric analysis. In addition, the later survey year serves as a robustness check on the first.